Evaluación de la terapia de ozono en pacientes caninos con enfermedad articular en rodilla - Pabón Carvajal, Maday Jacqueline (2016)
Ozone therapy is used today as a therapeutic method for treating various diseases. Results and effects change depending on the dose, concentration and route of application, which yield good results and fewer adverse effects. Enabled properties have even been used in the field of traumatology and orthopedics through a regenerative and antioxidant capacity that interrupts chronic inflammatory processes. In Ecuador there have been studies of ozone therapy with veterinary medicine, but not for the treatment of arthropathy. The objective of this study is to evaluate ozone therapy in canine patients with knee joint disease. Overall, ozone therapy was completed on 7 dogs referred to the Veterinary Hospital of the University of the Americas. A physical examination of the patients was performed and the functionality was assessed through a joint numerical scale for each session. After sedation of the patient, were taken samples of synovial fluid from the affected cytology were taken before and after treatment. Treatment consisted of 3 sessions with 1-2 intervals of ozone therapy per week applied intra-articularly. Finally, sedation was reversed with an antagonist drug to wake the patient. Improvement was observed in functional parameters and joint mobility limitation since the scores were decreasing progressively in sessions 2 and 3. Muscular atrophy in pelvic limbs remained constant at the end of the study. Based on cytological analysis there were no significant changes due to ozone therapy. In conclusion, ozone therapy is an effective therapeutic alternative for the treatment of knee joint disease and is also more affordable for the veterinarian and owner.